5c Factor Analysis Aspects Of The Designation Of Lending Of Working Capital In Pd. Bpr Bank Regional Lamongan - Izzati Choirini Mardhotillah (Jurnal Studi Manajemen dan Bisnis, 2019)
Credit evaluation is an important element in the provision of credit to the debtor. Lending activities, we need a good and thorough analysis of all aspects of credit to support the credit approval process, in order to prevent a credit risk. With its mission as an agent of development, banks are increasingly playing a role in the economy with increased lending to some sectors of the economy are priorities for improving the economy of the people and support the development of nasional.Tujuan of this study was to determine the creditworthiness conducted by the PD BPR Bank Regional Lamongan. From the analysis of the data using analytical tools 5C character, capacity, capital, collateral, condition states that the majority of borrowers eligible to receive a credit of PD. BPR lamongan Regional Banks. The credit approval process is a credit application by the debtor, research files, bank information search, site visits, analysis of credit research. If approved it will be an agreement or binding of collateral. Once it is done coaching supervision of credit or credit.Credit evaluation is an important element in the provision of credit to the debtor. Lending activities, we need a good and thorough analysis of all aspects of credit to support the credit approval process, in order to prevent a credit risk. With its mission as an agent of development, banks are increasingly playing a role in the economy with increased lending to some sectors of the economy are priorities for improving the economy of the people and support the development of nasional.Tujuan of this study was to determine the creditworthiness conducted by the PD BPR Bank Regional Lamongan. From the analysis of the data using analytical tools 5C character, capacity, capital, collateral, condition states that the majority of borrowers eligible to receive a credit of PD. BPR lamongan Regional Banks. The credit approval process is a credit application by the debtor, research files, bank information search, site visits, analysis of credit research. If approved it will be an agreement or binding of collateral. Once it is done coaching supervision of credit or credit.